2011
DOI: 10.1007/s00705-011-1149-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with hepatitis C virus infection in an urban population of the State of Mexico

Abstract: The aim of this study was to determine the seroprevalence anti-hepatitis C virus (HCV) antibodies and risk factors associated with patients attending primary-care clinics in the State of Mexico. A cross-sectional, prospective study was conducted on 10,524 consenting patients with history of at least one risk factor for HCV. Antibodies were detected by immunoassay, third-generation ELISA; RT-PCR was carried out to confirm HCV infection. The seroprevalence of HCV antibodies was 1.2% (128). The most common risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In recent studies done in Iran, the most prevalent genotype, was Type III[34] and studies in other countries including, Saudi Arabia revealed genotype IV as the most prevalent,[567] genotype Type II in Chinese and Brazilian prisoners,[89] Type II in Greek IVDUs[10] and Type I in other Countries. [11112]…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies done in Iran, the most prevalent genotype, was Type III[34] and studies in other countries including, Saudi Arabia revealed genotype IV as the most prevalent,[567] genotype Type II in Chinese and Brazilian prisoners,[89] Type II in Greek IVDUs[10] and Type I in other Countries. [11112]…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies of HCV performed in Mexican people that included blood donors, [28-30] open population, [31,32] and patients with cirrhosis [33] mentioned dental treatment as a probable risk factor. Other studies found that living with a family member infected with HCV [34,35] or suffering from liver disease [33,36,37] was an associated risk factor. Although it is known that multiple factors contribute to HCV transmissibility for saliva [5,38] and viral loads are very low in this [39].…”
Section: Discussionmentioning
confidence: 99%
“…The most common forms of viral transmission are related to the use of intravenous drugs, blood transfusion, multiple sexual partners, tattooing, piercings and perinatal origin (2). On the other hand in developing countries such as Mexico the most common cause of HCV transmission are blood transfusion and products (3).…”
Section: Introductionmentioning
confidence: 99%